The International Tundra Experiment (ITEX): 30 years of research on tundra ecosystems1 - Greg H.R. Henry; Robert D. Hollister; Kari Klanderud; Robert G. Björk; Anne D. Bjorkman; Cassandra Elphinstone; Ingibjörg Svala Jónsdóttir; Ulf Molau; Alessandro Petraglia; Steven F. Oberbauer; Christian Rixen; Philip A. Wookey (Arctic Science, 2022)
The International Tundra Experiment (ITEX) was founded in 1990 as a network of scientists studying responses of tundra ecosystems to ambient and experimental climate change at Arctic and alpine sites across the globe. Common measurement and experimental design protocols have facilitated synthesis of results across sites to gain biome-wide insights of climate change impacts on tundra. This special issue presents results from more than 30 years of ITEX research. The importance of snow regimes, bryophytes, and herbivory are highlighted, with new protocols and studies proposed. The increasing frequency and magnitude of extreme climate events is shown to have strong effects on plant reproduction. The most consistent plant trait response across sites is an increase in vegetation height, especially for shrubs. This will affect surface energy balance, carbon and nutrient dynamics and trophic level interactions. Common garden studies show adaptation responses in tundra species to climate change but they are species and regionally specific. Recommendations are made including establishing sites near northern communities to increase reciprocal engagement with local knowledge holders and establishing multi-factor experiments. The success of ITEX is based on collegial cooperation among researchers and the network remains focused on documenting and understanding impacts of environmental change on tundra ecosystems.